IMPROVING THE EFFICIENCY OF THE ORGANIZATION OF BENCHMARKING SERVICES IN INDUSTRIAL ENTERPRISES - Zulaykho A. Uktamjonova; Gulshoda K. Ismoilova (European Science Publishing, 2024)
In the conditions of the market economy, in the conditions of constant global competition, continuous improvement of industrial enterprises, optimization of competitive characteristics and production, creation of all internal capabilities, and preservation of competitive advantages are urgent tasks. The ambiguous side of this problem is that the emergence of new directions, methods and appropriate means of achieving and forming competitiveness led to the preservation of the advantage of the enterprise. One of the most effective tools that allows enterprises to constantly increase profitability, improve the quality of its results, outperform competitors, is the use of comparison technology.
Keywords: opportunities, constant global competition, benchmarking, enterprise advantage, business process analysis